ISU-ISU KRITIS MENUJU MASYARAKAT MADANI INDONESIA - Arba' atun (Universitas Islam Negeri Sumatera Utara Medan, 2017)
It is not coincindence if in the opening of the 1945th Constution said that the aim of creating the unitary Republic Indonesia is to the intellectual life of the nation. Intelligent nation is a nation that is produced by the educational system. Therefore, increasing the role of education in achieving a new Indonesian society is a manifestation of the reform movement of society and the nation of Indonesia. The new Indonesian society that we are building is Indoneisian civil society.